A novel sustainable biocide against the fruit fly Drosophila suzukii made from orange peels - Giovanni Davide Barone; Manfred Hartbauer (Scientific Reports)
Abstract Drosophila suzukii (D. suzukii), a pervasive pest originating from Southeast Asia, presents a substantial risk to global agriculture. The ability of the female flies to lay eggs within fruits of varying maturity stages, combined with the accelerated offspring development within warmer climates, results in rapid population growth. This poses significant challenges for fruit production and viticulture, exacerbated by the increasing prevalence of pesticide resistance. We propose a solution to this growing issue using an attract-and-kill approach by making use of upcycled organic waste materials made from orange peels. Specifically, we have tested an innovative salty orange peel product (OPP) in a choice experiment, in which OPP and hydrogel (control) were made available to fruit flies in Petri dishes situated beneath red wine grapes. The number of dead flies in both Petri dishes were counted each day and fly maggots inside berries were extracted after four days. Since Petri dishes were covered with a red lid, flies only selected on the basis of olfactory cues. Our results showed a higher number of captured flies in Petri dishes containing OPP compared to those with the hydrogel control. Furthermore, a notable reduction in the number of maggots was observed inside grapes located above OPP compared to the grapes closer to the hydrogel control. Dilution of OPP was followed by a lower count of dead flies. In additional choice experiments, the concentration of NaCl was found to be positively correlated with the number of dead flies. This suggests an important lethal effect caused by high salt concentrations. In a final experiment, OPP was also compared to the commercially-available attractant called Drosalure™, which resulted in a slightly higher attractiveness of OPP to D. suzukii. These findings suggest that OPP holds potential as a cost-efficient and eco-friendly biocide made from organic waste material. OPP offered in attract-and-kill traps equipped with small entry holes is safe for bees and may replace other less eco-friendly control measures for D. suzukii in organic vineyards.